2017
DOI: 10.1007/s11655-017-2414-z
|View full text |Cite
|
Sign up to set email alerts
|

Review on antioxidants and evaluation procedures

Abstract: Antioxidants are the substances that are capable of counteracting the damaging effects of the physiological process of oxidation occur in animal tissues. These may be nutrients (vitamins and minerals) as well as enzymes (proteins) in our body that assist in chemical reactions. They are believed to play a role in preventing the development of chronic diseases like cancer, diabetes, heart disease, stroke, Alzheimer's disease, rheumatoid arthritis, and cataracts etc. The present review article emphasizes on the v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 49 publications
1
24
0
3
Order By: Relevance
“…Both T1DM and T2DM present as a highly inflammatory and oxidative pathology, presenting a direct relation to cardiovascular events. In nondrug therapy, the use of antioxidants and phenolic compounds shows positive effects on redox action and has a protective effect on the heart tissue and prevents damage to it [76][77][78]. In the present study, both resistance training and supplementation and their combination demonstrated protective effects against the damage caused by reactive species to the cardiac tissue in T1DM.…”
Section: Discussionsupporting
confidence: 59%
“…Both T1DM and T2DM present as a highly inflammatory and oxidative pathology, presenting a direct relation to cardiovascular events. In nondrug therapy, the use of antioxidants and phenolic compounds shows positive effects on redox action and has a protective effect on the heart tissue and prevents damage to it [76][77][78]. In the present study, both resistance training and supplementation and their combination demonstrated protective effects against the damage caused by reactive species to the cardiac tissue in T1DM.…”
Section: Discussionsupporting
confidence: 59%
“…It can be observed that the main phenolic compounds that are present in maqui berries are anthocyanins, unlike many other berries that have less anthocyanin content in comparison with the total phenolic compounds. This high anthocyanin's content greatly contributes to their superior antioxidant capacity [7].…”
Section: Optimal Conditionsmentioning
confidence: 99%
“…Sunflower is characterized by anti‐inflammatory activity. The seeds of sunflowers are known to be rich in vitamin E and magnesium that serve as an excellent source of fat‐soluble antioxidant to the body (Kumar, Sharma, & Vasudeva, 2017). The antioxidant properties displayed by vitamin E neutralize the free radicals that may cause damage to the fat‐containing structures and molecules, such as cholesterol, brain cells, and cell membranes (Nowicka & Kruk, 2017).…”
Section: Nutritional Attributes and Health Importance Of Sunflowermentioning
confidence: 99%